TRPV1 activation counters diet-induced obesity through sirtuin-1 activation and PRDM-16 deacetylation in brown adipose tissue - Baskaran, P; Krishnan, V; Fettel, K; Gao, P; Zhu, Z; Ren, J; Thyagarajan, B (International Journal of Obesity, 2017)
Background/objective: An imbalance between energy intake and expenditure leads to obesity. Increasing metabolism and thermogenesis in brown adipose tissue (BAT) can help in overcoming obesity. Here, we investigated the effect of activation of transient receptor potential vanilloid subfamily 1 (TRPV1) in the upregulation of thermogenic proteins in BAT to counter diet-induced obesity. Subjects/methods: We investigated the effect of dietary supplementation of capsaicin (CAP) (TRPV1 agonist) on the expression of metabolically important thermogenic proteins in BAT of wild-type and TRPV1 −/− mice that received either a normal chow or high-fat (±CAP; TRPV1 activator) diet by immunoblotting. We measured the metabolic activity, respiratory quotient and BAT lipolysis. Results: CAP antagonized high-fat diet (HFD)-induced obesity without decreasing energy intake in mice. HFD suppressed TRPV1 expression and activity in BAT and CAP countered this effect. HFD-feeding caused glucose intolerance, hypercholesterolemia and decreased the plasma concentration of glucagon-like peptide-1 and CAP countered these effects. HFD suppressed the expression of metabolically important thermogenic genes, ucp-1, bmp8b, sirtuin-1 (SIRT-1), PPARγ coactivator 1α and PR domain containing zinc finger protein 16 (prdm-16) in BAT and CAP prevented this effect. CAP increased the phosphorylation of SIRT-1 and induced an interaction between peroxisome proliferator activated receptor gamma (PPARγ) with PRDM-16. Further, CAP treatment, in vitro , decreased the acetylation of PRDM-16, which was antagonized by inhibition of TRPV1 by capsazepine, chelation of intracellular Ca 2+ by cell permeable BAPTA-AM or the inhibition of SIRT-1 by EX527. Further, CAP supplementation, post HFD, promoted weight loss and enhanced the respiratory exchange ratio. CAP did not have any effect in TRPV1 −/− mice. Conclusions: Our data show that activation of TRPV1 in BAT enhances the expression of SIRT-1, which facilitates the deacetylation and interaction of PPARγ and PRDM-16. These data suggest that TRPV1 activation is a novel strategy to counter diet-induced obesity by enhancing metabolism and energy expenditure.